2007
DOI: 10.1111/j.1467-9280.2007.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Language is not Just for Talking

Abstract: In addition to having communicative functions, verbal labels may play a role in shaping concepts. Two experiments assessed whether the presence of labels affected category formation. Subjects learned to categorize "aliens" as those to be approached or those to be avoided. After accuracy feedback on each response was provided, a nonsense label was either presented or not. Providing nonsense category labels facilitated category learning even though the labels were redundant and all subjects had equivalent experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
112
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(119 citation statements)
references
References 35 publications
7
112
0
Order By: Relevance
“…A novel stimulus can be re-coded in terms of known constituents (e.g., “attractive, blond female”) but that encoded representation may not facilitate discrimination of targets from foils. Our view, that labels facilitate encoding because there is less of a burden on working memory resources (Reder et al, 2007), is consistent with an argument put forward by Lupyan (e.g., Lupyan, Rakison & McClelland, 2007). When contextual information is unavailable for recognition, judgments are based on a familiarity process.…”
Section: Introductionsupporting
confidence: 90%
“…A novel stimulus can be re-coded in terms of known constituents (e.g., “attractive, blond female”) but that encoded representation may not facilitate discrimination of targets from foils. Our view, that labels facilitate encoding because there is less of a burden on working memory resources (Reder et al, 2007), is consistent with an argument put forward by Lupyan (e.g., Lupyan, Rakison & McClelland, 2007). When contextual information is unavailable for recognition, judgments are based on a familiarity process.…”
Section: Introductionsupporting
confidence: 90%
“…For example, infants categorize better when the same name is paired with objects from the same category (Yoshida & Smith, 2005), even when these objects are perceptually dissimilar (Plunkett, Hu, & Cohen, 2008). Names also facilitate category learning for adults, even when names are not actively used during the learning task (Lupyan, Rakison, & McClelland, 2007).…”
mentioning
confidence: 99%
“…In other words, tightness of a fit is salient in Korean, while it is less important in English. McDonough et al (2003) found that while Korean-speaking adults had no difficulties in categorizing actions in terms of the tightness of fit, English-speaking adults had considerable difficulties in this regard.…”
Section: L1 Language-construal Interfacesmentioning
confidence: 89%
“…The evidence from the research has related the cross-linguistic Source: Wolff and Holmes (2011). differences in the ways speakers of a language categorize, sort, and perceive various entities to the way in which conceptual representations are packaged and presented by the speakers of the language. The research has been extended to various domains such as time (e.g., Miles et al, 2011), space (e.g., Haun et al, 2011), motion , color (Athanasopoulos et al, 2010), objects (Imai and Gentner, 1997), number (Gordon, 2004), and categorization (Lupyan et al, 2007).…”
Section: L1 Language-construal Interfacesmentioning
confidence: 99%